1991
DOI: 10.1007/bf00867171
|View full text |Cite
|
Sign up to set email alerts
|

Type A behavior and marital interaction: Hostile-dominant responses during conflict

Abstract: Previous research has indicated that the risk conferred by men's Type A versus B behavior depends, in part, on the personality characteristics of their spouses. In the present study of 60 married couples, we found that couples consisting of two Structured Interview-defined Type A's showed a larger increase in hostile/dominant behavior during discussions of marital conflicts than did couples consisting of two Type B's or a Type A husband and a Type B wife. Couples consisting of a Type B husband and a Type A wif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…Because external sources of social support, role captivity, and loss of self were not measured, possible explanations for the relation between restriction in outside activities and spousal NA await further research. The potential association between spousal negative mood and critical and avoidant responses toward the patient is consistent with studies illustrating a link between an individual's cynical hostility and conflict in the family context (Sanders et al, 1991;Smith, Pope, Sanders, Allred, & O'Keefe, 1988). The findings provide preliminary support for our hypothesis that the quality of the marital relationship moderated associations between functional impairment and spousal negative behaviors.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Because external sources of social support, role captivity, and loss of self were not measured, possible explanations for the relation between restriction in outside activities and spousal NA await further research. The potential association between spousal negative mood and critical and avoidant responses toward the patient is consistent with studies illustrating a link between an individual's cynical hostility and conflict in the family context (Sanders et al, 1991;Smith, Pope, Sanders, Allred, & O'Keefe, 1988). The findings provide preliminary support for our hypothesis that the quality of the marital relationship moderated associations between functional impairment and spousal negative behaviors.…”
Section: Discussionsupporting
confidence: 86%
“…The literature on social relationships of individuals with high levels of trait hostility may provide some support to the link between one aspect of negative mood, hostility, and critical interpersonal behavior. These studies have shown that hostility is associated with generally high levels of interpersonal conflict in the context of work, marriage, and family of origin (Houston & Kelly, 1987; Sanders, Smith, & Alexander, 1991). The link between emotional distress and the healthy partner’s unsupportive treatment of the ill partner in the context of a debilitating illness has been less studied.…”
mentioning
confidence: 99%
“…Medalie and Goldbourt (1976) in a 5‐year prospective study of marital quality and health, found that a wife's love and support was associated with a reduced risk for the development of angina pectoris in husbands. Sanders, Smith, and Alexander (1991) reported a relationship between marital hostile/dominant behavior and Type A or Type B personality pattern in both husbands and wives. Brown and Smith (1992) found a strong relationship between hostility during marital interaction and heart rate reactivity.…”
Section: The Core Content Areasmentioning
confidence: 99%
“…4. Hostility and Type‐A Personality: Sanders, Smith, and Alexander (1991) reported a relationship between marital hostile/dominant behavior and Type A or Type B personality pattern in both husbands and wives. Brown and Smith (1992) found a strong relationship between hostility during marital interaction and heart rate reactivity.…”
Section: The Core Content Areasmentioning
confidence: 99%